Luminosities and energies of e+e− collision data taken between =4.61 GeV and 4.95 GeV at BESIII*Supported in part by National Key R&D Program of China (2020YFA0406400, 2020YFA0406300); National Natural Science Foundation of China (NSFC) (11635010, 11735014, 11805086, 11835012, 11935015, 11935016, 11935018, 11961141012, 12022510, 12025502, 12035009, 12035013, 12192260, 12192261, 12192262, 12192263, 12192264, 12192265); the Chinese Academy of Sciences (CAS) Large-Scale Scientific Facility Program; Joint Large-Scale Scientific Facility Funds of the NSFC and CAS (U1832207); CAS Key Research Program of Frontier Sciences (QYZDJ-SSW-SLH040); 100 Talents Program of CAS; Fundamental Research Funds for the Central Universities, Lanzhou University, University of Chinese Academy of Sciences; The Institute of Nuclear and Particle Physics (INPAC) and Shanghai Key Laboratory for Particle Physics and Cosmology; ERC (758462); European Union's Horizon 2020 research and innovation programme under Marie Sklodowska-Curie grant agreement ( 894790); German Research Foundation DFG (443159800), Collaborative Research Center CRC 1044, GRK 2149; Istituto Nazionale di Fisica Nucleare, Italy; Ministry of Development of Turkey (DPT2006K-120470); National Science and Technology fund; National Science Research and Innovation Fund (NSRF) via the Program Management Unit for Human Resources & Institutional Development, Research and Innovation (B16F640076); STFC (United Kingdom); Suranaree University of Technology (SUT), Thailand Science Research and Innovation (TSRI), and National Science Research and Innovation Fund (NSRF) (160355); The Royal Society, UK (DH140054, DH160214); The Swedish Research Council; U. S. Department of Energy (DE-FG02-05ER41374). (1st November 2022) - Ablikim 麦, M. 迪娜; Achasov, M. N.; Adlarson, P.; Albrecht, M.; Aliberti, R.; Amoroso, A.; An 安, M. R. 美儒; An 安, Q. 琪; Bai 白, X. H. 旭红; Bai 白, Y. 羽; Bakina, O.; Baldini, Ferroli R.; et al.
Abstract: From December 2019 to June 2021, the BESIII experiment collected approximately 5.85 fb −1 of data at center-of-mass energies between 4.61 and 4.95 GeV. This is the highest collision energy BEPCII has reached to date. The accumulated annihilation data samples are useful for studying charmonium(-like) states and charmed-hadron decays. By adopting a novel method of analyzing the production of pairs in annihilation, the center-of-mass energies are measured with a precision of 0.6 MeV. Integrated luminosities are measured with a precision of better than 1% by analyzing the events of large-angle Bhabha scattering. These measurements provide important inputs to analyses based on these data samples.